Does higher endorsement with collaboration lead to better performance on collaborative problem solving? An explanatory item response approach to cross-cultural comparisons - Lu, Chang; Bulut, Okan (Frontiers in Psychology, 2024)
Collaborative problem solving (CPS) is an essential competency in the 21st century. However, the understanding of how cultural background shapes individuals' collaboration awareness and its relationship with collaborative problem-solving skills are underexplored by psychometrics.This study employs Explanatory Item Response Modeling to examine the impact of cultural orientations on students' endorsement with collaboration in PISA 2015. Results show that students endorsed valuing teamwork more than valuing relationships. Western countries with individualist cultures generally demonstrated higher endorsement with collaboration than Eastern countries with collectivist cultures. China has the highest collaboration endorsement, followed by the US, Canada, Korea, and Japan. In contrast, Japan has the highest CPS assessment scores, followed by Korea, Canada, the US, and China. Findings revealed that students from collectivist cultures don't have higher endorsements of collaboration compared with students from individualist cultures. Also, higher endorsement of collaboration does not necessarily lead to better success in the CPS assessment. Further research is needed to understand the gap between students' attitudes toward collaboration and their achievement based on cultural values and schools' CPS training.